Knowledge, innovation and collective learning: theory and evidence from three different productive areas in Italy - Roberta Capello; Alessandra Faggian (European Regional Science Association (ERSA), 2002)
Innovative capacity of firms has traditionally been explained through intra-firm characteristics, being firms size the most important. A wave of empirical studies identifies small firms as the engines of technological change and innovative activity, at least in certain industries. This statement and these empirical findings constrast the well known observation that, since R&D expenditure is concentrated in large firms, and that innovative output strongly depends on R&D inputs, large firms are expected to drive the technological process. These contrasting results have pushed industrial economists to look for other explanatory variables. In the recent literature much emphasis has been put to determinats which are external to the firm; these external factors are called knowledge spillovers, and refer to the positive externalities that firms receive in terms of knowledge from the environment in which it operates. Both industrial and regional economists underline the importance of knowledge spillovers. As this paper underlines, the main difference between the two groups is that regional economists identify in a clear way the channels through which knowledge spills over a local area. The concept of relational capital is fundamental in this respect. Relation capital is in fact defined as the set of all relationships - market relationships, power relationships, co-operation - established between firms, institutions and people, which stem from a strong sense of belonging and a highly developed capacity of cooperation typical of culturally similar people and institutions. The existence of high relational capital in an area generates stable cooperation between firms and their local suppliers and customers, an efficient local labour market with a high internal mobility of employees and spin-offs from local firms, which are considered as the main channels through which knowledge spreads over a local area. Thus regional economists provide a new insight in the way knowledge develops over space; from the empirical point of view, some qualitative case studies exist which stress collective learning mechanisms, but a real need exists for solid quantitative empirical analyses. The main aims of the present paper are twofold. The first aim is o underline the main differences between industrial and regional economists. The second aim is to provide a quantitative empirical approach using econometric techniques to verify the existence and importance of relational capital on the innovation activity of firms. Proxies are found to represent the channels of collective knowledge and therefore indirectly of relational capital. The different regional, sectoral and firms' characteristics will also be analysed, in order to understand whether they influence the role relational capital has on firms' innovation. It is, indeed, reasonable to expect that relational capital will play a different role in different regional, sectoral and firm's contexts.
Keywords: 330